Comparative physiological activity and productivity of two local West Timor (Indonesia) maize in response to t'sen, row, and monoculture cropping patterns - YOHANNIS HARRY DIMU-HEO; DIDIK INDRADEWA; EKA TARWACA SUSILO PUTRA; BENITO HERU PURWANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Dimu-Heo YH, Indradewa D, Putra ETS, Purwanto BH. 2024. Comparative physiological activity and productivity of two local West Timor (Indonesia) maize in response to t'sen, row, and monoculture cropping patterns. Biodiversitas 25: 1718-1728. T'sen is a traditional cropping pattern practiced in West Timor, where farmers plant maize, cowpeas, and pumpkins together in one hole. Field research was carried out to compare the productivity and physiological activity of maize grown in monoculture, t'sen, and row cropping patterns. The research followed a split-plot design with four replications. The main plot consisted of monoculture, t'sen, and row cropping patterns, while the subplots included local maize varieties: Kupang and TTS. The results showed that the t'sen cropping pattern did not cause any differences in stomatal activity, chlorophyll properties, transpiration rate, and photosynthesis rate, resulting in productivity that was not significantly different from monoculture. In contrast, the row cropping pattern led to an increase in the width of the stomatal opening but caused a decrease in the rate of transpiration and photosynthesis, resulting in lower productivity compared to monoculture. Additionally, the research found the productivity of the Kupang variety was higher than the TTS variety. Furthermore, both cropping patterns resulted in higher total protein yields due to cowpea and pumpkin fruit production compared to monoculture, with the t'sen showing significantly higher than the row cropping pattern.